The ethnic diversities in animal-human interactions in former Jammu and Kashmir State- India - Hassan, Musheerul; Haq, Shiekh Marifatul; Yakoob, Umer; Altaf, Muhammad; Bussmann, Rainer W (Ethnobotany Research and Applications, 2021)
Background: Cultural diversity in the Himalayan Mountain regions is closely linked to biodiversity, as there is a very close relationship between the local fauna and cultures. Religious rules and rituals also reinforce this relationship. Research has proven that these relationships are complex and differ based on a variety of factors. Methods: There has been almost no research to explain the animal human interaction and commercially important animal species in different ethnic communities of Jammu and Kashmir. The present study was conducted throughout 2019–2020 and data were gathered through open and closed-end semi-structured interviews and group discussions. Results: We found 10 species of mammals, 7 species of birds, and 7 species of fish were commercially important and playing a vital role in the economy of the local ethnic communities (Kashmiri, Pahari, Hanji, Bakarwal, Changapa). Among the documented species, seven species were unique to Hanji, followed by 4 species to Pahari, 3 to Kashmiri and 2 species to Changapa. The heat map classified predators into three groups that were recognized on the basis of indicator species. Eight main predators (Selenarctos thibetanus, Vulpes vulpes, Herpestes auropunctatus, Canis familiaris, Felis catus, Canis lupus, Panthera uncia, and Panthera pardus) preying the documented species were recorded across the entire study area. Bos taurus primigenius, Bos Taurus and Gallus gallus domesticus played a significant role in the cultural and religious ritual aspects, whereas Capra aegagrus hircus, Equus ferus caballus and Gallus gallus domesticus were commonly used as a livelihood source among local communities. Conclusions: Present study enlightened the interaction between the local fauna and cultures, meanwhile the study is first in its kind to document the livestock species with commercial value and specific communities associated with them in the former state Jammu and Kashmir. Keywords: Commercial species; Economy; Ethnic groups, Jammu and Kashmir